Penerapan Role-Based Access Control (RBAC) untuk Mengelola Hak Akses pada Sistem Informasi Sekolah Taman Kanak-Kanak Berbasis Multiuser: Implementasi Mekanisme Kontrol Akses Berbasis Peran pada Lingkungan Multiuser - Sri Ramadhani; Dedy Armiady; Riyadhul Fajri (Fakultas Ilmu Komputer Universitas Almuslim, 2026)
This study aims to design and implement a multiuser information system based on Role-Based Access Control (RBAC) in a kindergarten (TK) environment to manage user access rights in a structured and secure manner. In multiuser-based school information systems, improper access control can lead to unauthorized data access, role conflicts, and security vulnerabilities. To address this issue, this research applies RBAC as the main authorization mechanism, where access rights are granted based on predefined user roles. The system is developed using a software engineering approach with a descriptive methodology, following stages of requirements analysis, system design, implementation, and testing. Three primary roles are defined in the system: Super Admin, School Admin, and Operator, each with different access privileges. The system is implemented using PHP with the CodeIgniter framework and MySQL as the database management system. To enhance responsiveness and accuracy in access control enforcement, a real-time mechanism using Pusher.js is integrated to synchronize access right changes without requiring manual page refresh. System testing is conducted using black-box testing to verify access restrictions, menu visibility, and data isolation between schools. The results show that the RBAC mechanism functions effectively in restricting access according to user roles, preventing unauthorized actions, and ensuring data separation across institutions. This research demonstrates that RBAC can be reliably applied as a foundational access control model for multiuser school information systems, particularly in early childhood education environments, and can be further developed for real-world implementation.